Fabrication of Periodic Nanostructure Assemblies by Interfacial Energy Driven Colloidal Lithography. (22nd April 2014) - Dev, A.; Dev Choudhury, B.; Abedin, A.; Anand, S.
<x xml:space="preserve">Abstract</x> A novel interfacial energy driven colloidal lithography technique to fabricate periodic patterns from solution‐phase is presented and the feasibility and versatility of the technique is demonstrated by fabricating periodically arranged ZnO nanowire ensembles on Si substrates. The pattern fabrication method exploits different interfaces formed by sol–gel derived ZnO seed solution on a hydrophobic Si surface covered by a monolayer of colloidal silica spheres. While the hydrophobic Si surface prevents wetting by the seed solution, the wedge shaped regions surrounding the contact point between the colloidal particles and the Si substrate trap the solution due to interfacial forces. This technique allows fabrication of uniform 2D micropatterns of ZnO seed particles on the Si substrate. A hydrothermal technique is then used to grow well‐defined periodic assemblies of ZnO nanowires. Tunability is demonstrated in the dimensions of the patterns by using silica spheres with different diameters. The experimental data show that the periodic ZnO nanowire assembly suppresses the total reflectivity of bare Si by more than a factor of 2 in the wavelength range 400–1300 nm. Finite‐difference time‐domain simulations of the wavelength‐dependent reflectivity show good qualitative agreement with the experiments. The demonstrated method is also applicable for other materials synthesized by solution chemistry.